2020
DOI: 10.1080/15140326.2020.1722384
|View full text |Cite
|
Sign up to set email alerts
|

Merchandise exports and economic growth: multivariate time series analysis for the United Arab Emirates

Abstract: This paper examines the validity of the export-led growth (ELG) hypothesis in the United Arab Emirates (UAE) over the period 1975-2012, using a neoclassical production function augmented with merchandise exports and imports of goods and services. The study applies the Johansen cointegration technique and dynamic ordinary least squares (DOLS) regression to confirm the existence of a long-run relationship between exports and economic growth, while the multivariate Granger causality test is applied to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 75 publications
2
30
0
Order By: Relevance
“…However, the findings of such studies remain at best inconclusive and often contradictory. Broadly speaking, previous studies on this subject can be divided into Lanka; El-Sakka and for Kuwait, Libya, Qatar, Sudan and Tunis; Shirazi and Manap (2005) for Sri Lanka and India; Tang (2006) for China; Tang (2006) for China; Shirazi and Manap (2005) for Sri Lanka and India; more recently, Kalaitzi and Chamberlain (2020) for the case of the United Arab Emirates in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the findings of such studies remain at best inconclusive and often contradictory. Broadly speaking, previous studies on this subject can be divided into Lanka; El-Sakka and for Kuwait, Libya, Qatar, Sudan and Tunis; Shirazi and Manap (2005) for Sri Lanka and India; Tang (2006) for China; Tang (2006) for China; Shirazi and Manap (2005) for Sri Lanka and India; more recently, Kalaitzi and Chamberlain (2020) for the case of the United Arab Emirates in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical model was derived from neo-classical growth theory and is based on a Cobb-Douglas production function with constant returns to scale [45,55]. Exports were assumed to impact the output via an effect on total factor productivity (TFP).…”
Section: Empirical Methodologymentioning
confidence: 99%
“…These findings are consistent with the early work of [44], who reported that exports exert a negative impact on the economic growth of Asian and African countries. One reason brought forward [44,45] for this negative impact is that less-developed countries primarily focus on exporting primary goods whose prices are heavily volatile, which, in turn, leads to volatile export revenues and increased economic uncertainty.…”
Section: The Export-led Growth Hypothesis and Its Empirical Supportmentioning
confidence: 99%
“…Some of the previous empirical studies have aimed to test the validity of the export-led growth hypothesis for the UAE economy by using either of the following; manufactured exports, total exports or non-oil exports as focal variables (Alodadi, A. A. S. (2016); Kalaitzi, A. S., and Cleeve, E. (2018); Kalaitzi, A. S., and Chamberlain, T. W. (2020); Kalaitzi, A. 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings of some existing studies reveal that exports play a crucial role in the economic growth of the UAE. For instance, Kalaitzi, A. S., & Chamberlain, T. W. (2020) in their study on the role of exports on the economic growth of the UAE examine the impact of merchandise exports on economic growth for the period 1975-2012 in order to test the validity of the Export-Led Growth Hypothesis for the UAE economy. The study incorporates the Cointegration test, ECM, and dynamic ordinary least squares test to confirm the long-run relationship between UAE exports and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%